Northern exposure. Season five [videorecording (DVD)]. - Morrow, Rob; Turner, Janine, 1963-; Corbett, John, 1961-; Corbin, Barry, 1940-; Cullum, John, 1930- (Universal Studios Home Entertainment, 2013)
Reunite with Dr. Joel Fleischman, Maggie, Chris, and the rest of the quirky residents of Cicely, Alaska.